Low-Dimensional Nanomaterial Systems Formed by IVA Group Elements Allow Energy Conversion Materials to Flourish - Dan Li; Jinsheng Lv; Mengfan Shi; Liru Wang; Tian Yang; Ya’nan Yang; Nan Chen (Nanomaterials, 2022)
In response to the exhaustion of traditional energy, green and efficient energy conversion has attracted growing attention. The IVA group elements, especially carbon, are widely distributed and stable in the earth’s crust, and have received a lot of attention from scientists. The low-dimensional structures composed of IVA group elements have special energy band structure and electrical properties, which allow them to show more excellent performance in the fields of energy conversion. In recent years, the diversification of synthesis and optimization of properties of IVA group elements low-dimensional nanomaterials (IVA-LD) contributed to the flourishing development of related fields. This paper reviews the properties and synthesis methods of IVA-LD for energy conversion devices, as well as their current applications in major fields such as ion battery, moisture electricity generation, and solar-driven evaporation. Finally, the prospects and challenges faced by the IVA-LD in the field of energy conversion are discussed.